2017
DOI: 10.1016/j.jrras.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Latent effect of gamma irradiation on reproductive potential and ultrastructure of males' testes of Culex pipiens (Diptera; Culicidae)

Abstract: View related articles View Crossmark data Citing articles: 7 View citing articles Latent effect of gamma irradiation on reproductive potential and ultrastructure of males' testes of Culex pipiens (Diptera; Culicidae

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
4
9
0
Order By: Relevance
“…(Bao and Dolder, 1991), According to Chapman (1998), the muscular layer may contribute to the displacement of the spermatid bundle in order to free spermatozoa into the testes and toward the posterior duct to lead out of the testis. This structure not only described in tephritidae, the same aspects of testicular organization were described in other species such as on Culex pipiens (Hassan et al, 2017) and on Blaps sulcata (Kheirallah et al 2017). Moreover, the present study confirmed the organizational pattern of mitochondrial derivatives with axoneme that was observed in the flagellate spermatozoa.…”
Section: Ultrastructure Studiessupporting
confidence: 89%
See 1 more Smart Citation
“…(Bao and Dolder, 1991), According to Chapman (1998), the muscular layer may contribute to the displacement of the spermatid bundle in order to free spermatozoa into the testes and toward the posterior duct to lead out of the testis. This structure not only described in tephritidae, the same aspects of testicular organization were described in other species such as on Culex pipiens (Hassan et al, 2017) and on Blaps sulcata (Kheirallah et al 2017). Moreover, the present study confirmed the organizational pattern of mitochondrial derivatives with axoneme that was observed in the flagellate spermatozoa.…”
Section: Ultrastructure Studiessupporting
confidence: 89%
“…The testis structure of B. zonata appeared the same of those previously studied on Tephritidae species by Bairati (1967) on Drosophila melanogaster, Valdez (2001) on Anastrepha ludens, Hassan et al, (2017) on Culex pipiens. The result cleared that the testis of B. zonata contained an external wall surrounded the germ cells.…”
Section: Ultrastructure Studiessupporting
confidence: 79%
“…F1 sterility of irradiated Spodoptera litura was higher than P sterility and that F1 males inherited more sterility than did F1 females (Seth & Sharma, 2001). The acquired deleterious impacts of gamma radiation were seen in the F1, F2 and F3 generations of Culex pipiens (Hassan, Mounier, Kotb, Gabarty, & Tharwat, 2016).…”
Section: Biological Studiesmentioning
confidence: 99%
“…Histopathological effects of gamma radiation on spermatogenesis in the Dipteran insect, Culex pipiens were recorded. Abnormal distributions of the developmental stages of spermatogonia and spermatocytes led to a general decrease in the rate of spermatogenesis, deformity of sperm, inhibiting the sperm movements and reduce the fertility (Hassan et al, 2016).…”
Section: Ultrastructure Studiesmentioning
confidence: 99%
“…It is evident that gamma radiation affects normal growth, development, and reproduction of insects (Hallman, 2003;Helinski et al, 2009;Kheirallah, 2016;Kheirallah et al, 2017) and may cause either sterility or mortality (Prabhakumary et al, 2011;Sengupta, 2013;Mohamed et al, 2014). A paucity of investigations reported the effect of gamma radiation on the histological and ultrastructure of insects (Paoli et al, 2014;Kheirallah 2016;Hassan et al, 2017;Kheirallah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%